Analisis Penilaian Persediaan Barang Dagang Produk Johnson & Johnson Dengan Metode FIFO Pada Distributor PT Supralita Mandiri (International Forum of Researchers and Lecturers, 2023)
The purpose of this study was to analyze Johnson & Johnson's stock of trade goods and analyze the assessment of Johnson & Johnson's stock of trade goods using FIFO method on distributor PT Supralita Mandiri. This study used a type of case study with a qualitative approach. The data collection techniques used are interviews and documentation. This study used secondary data.The results of this study show that PT Supralita Mandiri has 115 products and is divided into two, namely baby care and adult care, where baby care has 7 types of products with 69 products and adult care has 5 types of products with 46 products. The Standard Operational Procedure (SOP) set by PT Supralita Mandiri for inventory registration is to use the perpetual method and the inventory assessment is to use the First In First Out (FIFO) method. Operatively the company has implemented FIFO methods in accordance with the company's SOP. However, on the goods supply card, the company has not implemented the FIFO method.